Influence of Poynting-Robertson Drag and Oblateness on Existence and Stability of Out of Plane Equilibrium Points in Spatial Elliptic Restricted Three Body Problem - Chakraborty, A.; Narayan, A. (Journal of Informatics and Mathematical Sciences, 2018)
This paper studies existence and stability of the out of plane equilibrium points \(L_{6,7}\) analytically and numerically in the elliptical restricted three body problem, where both the primaries are radiating oblate spheroid, incorporating the effects of Poynting-Robertson (P-R) drag of the radiating primaries as well. It is observed that consideration of PR-drag forces results in the non-zero y-coordinate of the out of plane equilibrium points. The stability of the equilibrium points is studied in presence of PR-drag forces. Also the stability is further analyzed in the case when the PR-drag forces are neglected. We have explored the existence of out of plane equilibrium points and their stability around the binary systems: Luyten-726 and Sirius.